Outcomes of Preoperative Embolization of Juvenile Nasopharyngeal Angiofibroma - Sajad Younis Al-Helo; Hameed Dikhil Hussein Al shammary; Raman Agab Aljanabi; Hibba Khalil Ibrahim (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: These are rare fibro-vascular neoplasms, out of all head and neck tumors, JNA contributingfor only less than 0.5%. JNA incidence rate almost 1/150,000 and affects men and adolescents’ malesObjectives: To study outcome and the role of Pre-operative Embolization of surgeries for JuvenileNasopharyngeal Angiofibroma.Methods: A retrospective cross sectional study conducted at Al-Sader Medical City during the period 2010through 2020 included 15 male patients who were managed for JNA, in whom embolization was performedpreoperatively.Results: The study included 15 male patients with an average age of 16.4 ± 3.1 (standard deviation) (range:11-22) years. The duration of the procedure is 126 minutes, on average and ranged 75 to 180 minutes;Average intra-operative blood loss was 300 (range: 150-750) ml. The postoperative hospitalization periodwas 2 days in 14 cases and a recurrence rate of 13.3% was reported.Conclusions: The use of preoperative embolization in JNA patients has been very beneficial in shorteningsurgery time, improve bloodless of the operative site, with a significant reduction in intraoperative bloodloss, reduction in postoperative hospitalization time, and reduction in recurrent rate.